Science Year By Year - Gifford, Clive ; Kennedy, Susan and Parker, Philip; Consultant Challoner, Jack (New York DK, 2017)
Packed with fascinating discoveries and facts, this visual reference takes kids on a fantastic journey through time, from stone tools and simple machines to space travel and robots.--
Include Color Illustration, Index and Glossary
Keywords: Discoveries in science -- Scientists -- Science